Reviving consumer-alienation in the discourse of consumers' negativity. (November 2019) - Junaid, Muhammad; Hou, Fujun; Hussain, Khalid
Consumer-alienation is a philosophically competent and efficacious concept capable of unfolding the domains of phenomena that can be disregarded simply at the cost of impoverishing the potentials of theoretical manifestation and explanation. Consumer-alienation is an impeded appropriation of consumer and brand; as a foundational concept, it serves not only as an analytic but as a descriptive and explanatory phenomenon, the key to understand rising consumer angst toward brand.